Rare Vascular Complication Leading to Leg Ischemia Post-Varicocelectomy - Al-Wahbi, Abdullah M.; Elmoukaied, Shaza (Medicine and Medical Research: New Perspectives Vol. 1, 2024)
Varicocelectomy is the most commonly performed operation for the treatment of male infertility. The causes of varicocele are multifactorial, but in the end, the result is a pathological dilatation of the veins draining the testicles. Many surgical approaches are used as each of them has advantages over the other and is preferred by surgeons. Vascular injury has never been reported as a complication of varicocelectomy apart from testicular artery injury. We present a 36-year-old male who developed leg ischemia post-varicocelectomy due to a common femoral artery injury. He was successfully treated by using a vein graft. In a literature review, over 5,000 patients pooled from 33 studies of varicocelectomy were evaluated. There were no vascular complications, and scrotal hematoma was very rare.